Physical education curriculum and fundamental motor skills performance level in Macedonian school children - Klincharov, Ilija; Aceski, Aleksandar; Jovanovski, Jovan; Vuksanovikj, Vladimir (Факултет за спорт и физичко васпитање у Лепосавићу, Универзитет у Приштини – Косовска Митровица, 2019)
Physical education in the early school age children should be directed towards learning and developing the fundamental motor skills. In the later period of schooling, these learned and appropriately developed motor skills, should provide a basis for upgrading a number of specialized motor forms of complex type (combinations of fundamental movement skills, sports techniques from various sports). In order to assess the current situation, an initial analysis was made among pupils from 1-5 grade (classroom teaching phase in basic education) on the territory of the city of Skopje. Video analyzes of the performance of 12 fundamental locomotor and manipulative movements skills from the Test of Gross Motor Development battery (Ulrich 2000) were performed. The initial observations indicate a low level of proficiency in analyzed movement manifestations in all age categories. The conclusions are that the urgent revision and redesign of the national PE curriculum is required. The definition of clear motor skills performance standards (expected results) for each teaching topic in the appropriate age (grade) should be done. It is also necessary to raise the quality of PE curriculum application through quality professional work of the teachers, as well as with supply of adequate material conditions (facilities, equipment and requisites) for the realization of the PE curriculum.
Наставни програм физичког васпитања и ниво извебде основних моторичких вештина македонске школске деце
Book of Abstract
Keywords: physical education; curriculum; fundamental; motor skills